Pilates: efeitos na forca e imagem corporal de mulheres sedentárias - Souza, Catiane (2020)
The present study had the objective to assess the body image and overall strength of inexperienced practitioners along 30 Pilates sessions. 19 sedentary woman, naive to the method, with ages between 21 and 35 were submitted to 30 classic Pilates classes, in groups of four, twice a week. The evaluations took place in five occasions: before a month-long control period, before the intervention and after 10, 20 and 30 sessions. Gripstrenght was evaluated as representative for overall strength, complimentary to trunk extensors and body image assessed, with a body image scale, by the difference between the current self-assigned body image and the one considered ideal. Over 30 classical Pilates sessions trunk extensor strength presented statistical difference and big effect size between pre and post-intervention periods (T = 9,50; r = -0,537; z = -3,311; p = 0,001). Body image and gripstrenght did not differ.